1998
DOI: 10.1016/s0377-1237(17)30546-4
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Prostatic Specific Antigen (Psa) in Clinical Practice : Our Experience

Abstract: A total of89 patients in the age group of50-92 years having different histopathologically proven prostatic conditions were analysed with prostate specific antigen (PSA) and clinical co-relation undertaken. PSA levels were found to be significantly higher (p < 0.05) in 48 carcinoma prostate cases (mean 93.16 ± 50.75 nglml) as compared to 32 benign prostatic hyperplasia (mean 4.66 ± 3.85 nglml). Similarly, levels were considerably reduced in IS post-operative adenocarcinoma cases (mean 10.77 ± 9.65 nglml) as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Chopra GS et at in their study stated that in 48 cases of carcinoma prostate PSA level ranged from 8.4 to 260 ng/mL with mean 74.75 ± 59.39 ng/mL and in BPH PSA levels ranged from 0.2 to 14.5 ng/mL (mean 4.66 ± 3.85). 13 Up till now, the Gleason score and grade groups are strong predictors for disease progression, and the most important parameters in therapeutic decision-making. 14 In our study, 50% of cases showed Gleason's score 9 followed by Gleason's score 7 (23%) and score 8 (17%).…”
Section: Discussionmentioning
confidence: 99%
“…Chopra GS et at in their study stated that in 48 cases of carcinoma prostate PSA level ranged from 8.4 to 260 ng/mL with mean 74.75 ± 59.39 ng/mL and in BPH PSA levels ranged from 0.2 to 14.5 ng/mL (mean 4.66 ± 3.85). 13 Up till now, the Gleason score and grade groups are strong predictors for disease progression, and the most important parameters in therapeutic decision-making. 14 In our study, 50% of cases showed Gleason's score 9 followed by Gleason's score 7 (23%) and score 8 (17%).…”
Section: Discussionmentioning
confidence: 99%
“…The GLOBOCAN 2018 report estimated that there would be approximately 1.3 million new prostate cancer cases and 359,000 related deaths globally in 2018, which led to PCa being classified as the second most frequent cancer and the fifth leading cause of cancer deaths among men [4]. Also, the report demonstrated that about two-thirds of the newly diagnosed cases will be determined in the countries with very high developing index, where only 18% of the world’s male population resides [5, 6].…”
Section: Introductionmentioning
confidence: 99%